A review of recent large-scale systematic UK classroom observations, method and findings, utility and impact. Issue 4 (1st October 2020) - Apter, Brian; Sulla, Francesco; Swinson, Jeremy
ABSTRACT: Recent systematic observations of UK classrooms are reviewed. Findings about how verbal teacher-feedback and students' on-task behaviour are associated are discussed. The method, utility and impact of this type of quantitative research are discussed using a large-scale (mass) secondary school study. Findings include: the use of positive feedback by secondary teachers was not associated with students staying on-task more; teachers who talked more when teaching was not associated with students staying on-task more; secondary teachers use positive or critical verbal feedback in relation to academic work and/or behaviour proportionately in similar ratios to primary teachers; students are more on-task with more experienced teachers; more experienced teachers use more verbal behaviour including verbal feedback; teachers use less verbal feedback in inverse proportion to year-group seniority; older secondary students (by year group) are less on-task – irrespective of teacher feedback; secondary students are less on-task (78.15%) than primary students (85.23%).